(untitled) (Research, Society and Development, 2021)
This systematic review aimed to study the survival time of the virus from the coronavidae family on various materials and surfaces, thus enabling the adoption of preventive measures mainly in public environments. The electronic databases selected as a source of information were PubMed/Medline, Excerpta Medica database (EMBASE), Latin American and Caribbean Literature in Health Sciences (LILACS), Web of Science, Scopus, and LIVIVO; grey literature (Google Scholar, ProQuest, and OpenGrey) was also examined. The last electronic search of the six databases retrieved 4287 references. After removing the duplicate references, the titles and abstracts (phase 1) were read, and 37 articles were selected for complete reading (phase 2), which resulted in 13 included studies. All the studies evaluated coronavirus survival on the following surfaces and objects: stainless steel, glass, plastic, wood, metal, cloth, paper, cotton, latex, polystyrene petri dish, aluminium, copper, cardboard, Teflon, polyvinyl chloride (PVC), silicone rubber and disposable fabric. On surfaces such as glass, plastic, and steel, the virus has greater stability than it does on copper, fabric, paper, and cardboard. The conditions of temperature, relative humidity, absorption power, and texture were also considered important factors in the survival of the virus.